Government Initiatives for Enhancing Building Information Modeling Adoption in Saudi Arabia - Algahtany, Mohammed; Afiqah, R. Radzi; Al-Mohammad, Mohammad S.; Rahimi, A. Rahman (MDPI, 2023)
Despite its numerous benefits, many countries are slow in adopting building information modeling (BIM). As a result, policymakers are implementing different government initiatives (GIs) for enhancing BIM adoption globally. However, it is critical to exercise caution when implementing GIs due to each country’s specific requirements and rules. Having country-specific GIs can ensure that BIM is appropriately adopted and fits a country’s needs and problems. Therefore, this study aims to investigate the effectiveness of the GIs in enhancing BIM adoption in Saudi Arabia. Data from 101 industry professionals were analyzed using a mean ranking analysis, normalization method, exploratory factor analysis (EFA), and fuzzy synthetic evaluation (FSE). Five critical GIs for enhancing BIM adoption were identified: developing programs for improving BIM competencies, developing programs to increase BIM awareness and understanding, developing programs to integrate BIM into education curricula and academia, developing BIM-related contractual frameworks, and providing financial aid to reduce the cost of BIM adoption. The EFA results indicate that the GIs can be grouped into two underlying constructs: national policies and organizational strategies. The FSE results confirmed that all GIs are effective. The study findings can serve as a significant reference for industry practitioners and policymakers in assuring successful BIM adoption.